THE ESSENCE OF INDEPENDENT STUDY SKILLS ACTIVITIES IN THE TEACHING PROCESS OF FOREIGN LANGUAGES (Archive of Conferences, 2021)
The article is about the essence of independent study skills activities in the process of teaching students of higher education institutions.